Quality of life in Patients with Melasma: A Hospital-Based Study - Priyanka Mainali; Anil Kumar Jha; Shristi Shrestha; Deeptara Pathak Thapa; Smita Joshi; Bibush Amatya (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Melasma is the most common cause of facial melanosis and one of the most common diseases presenting to the Dermatology department. It can lead to psychological and emotional distress for the patients and can hamper their quality of life. So, this study was done to assess the quality of life among patients with melasma so that the need for couseling of these patients could be assessed along with medical treatment.